A case report of small bowel perforation secondary to cytomegalovirus related immune reconstitution inflammatory syndrome in an AIDS patient - Gutiérrez Delgado, Eva María; Villanueva Lozano, Hiram; García Rojas Acosta, Miguel J.; Miranda Maldonado, Ivett C.; Ramos Jiménez, Javier (2017)
Non-traumatic small bowel perforation is rare in adults but carries a high morbidity and mortality. The diagnosis is made on clinical suspicion, and the most common causes in developing countries are infectious diseases, being cytomegalovirus infection in immunocompromised patients the main etiology. We describe a patient with a recently diagnosed advanced stage HIV infection and an intestinal perforation associated with cytomegalovirus immune reconstitution inflammatory syndrome after highly active antiretroviral therapy initiation.